2001
DOI: 10.1093/ps/80.10.1463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation of Two Different Sources of Phytase on Egg Production Parameters in Laying Hens and Nutrient Digestiblity

Abstract: Hens were fed corn-soybean meal diets containing 0.35, 0.25, 0.15, or 0.10% nonphytate phosphorus (NPP) (40 to 60 wk). Phytases A and B were added at 0.25, 0.15, and 0.10% at 250 to 300 units of phytase (FTU)/kg feed in a 3 x 3 factorial; 0.35% was a control diet. Treatments were replicated with eight cages per treatment (five hens per cage) in a randomized complete block design. Phytase supplementation had a significant effect on several production parameters: feed intake, feed conversion, and egg mass. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 15 publications
9
41
3
1
Order By: Relevance
“…This is consistent with the findings of other authors who found that feed intake increased in hens fed diets containing 0.1% NPP supplemented with A. niger phytase (Gordon and Roland, 1997;Jalal and Scheideler, 2001). Table 1 Throughout the entire experimental period (20-44 weeks), the values of feed conversion ratio calculated for one g of egg (Table 5) were much better in the control and in all phytase-supplemented treatments (ECP 125 -ECP 500 ) compared with the D group, reaching 7.3% in group C, 5.6% in treatment ECP 125 , 6.0% in treatment ECP 250 and about 4.3% in treatment ECP 500 .…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with the findings of other authors who found that feed intake increased in hens fed diets containing 0.1% NPP supplemented with A. niger phytase (Gordon and Roland, 1997;Jalal and Scheideler, 2001). Table 1 Throughout the entire experimental period (20-44 weeks), the values of feed conversion ratio calculated for one g of egg (Table 5) were much better in the control and in all phytase-supplemented treatments (ECP 125 -ECP 500 ) compared with the D group, reaching 7.3% in group C, 5.6% in treatment ECP 125 , 6.0% in treatment ECP 250 and about 4.3% in treatment ECP 500 .…”
Section: Resultssupporting
confidence: 93%
“…Some authors have reported that a low dietary AP without supplemental F decreased performance characteristics, such as egg production, feed consumption or egg weight (Summers, 1995;Gordon and Roland, 1998;Boling et al, 2000;Francesch et al, 2005). In contrast, an increase in egg production, feed consumption, and egg weight (Um and Paik, 1999;Cabuk et al, 2004) and an improvement in the feed conversion (Jalal and Scheideler, 2001;Liebert et al, 2005) were found after F addition. The reduction of the feed conversion ratio and increase of the egg weight due to the F supplement is also evident from our results.…”
Section: Discussionmentioning
confidence: 99%
“…Phytase is commonly supplemented in laying hen diets to improve phytate phosphorus (P) availability and retention and ultimately to reduce excretion (Ravindran et al, 2000, Jalal and Scheideler, 2001, Gao et al, 2013, Gosh et al, 2015. Phytate is the main phosphorus source in the plant-based feed ingredients, which not only has limited availability to laying hens, but can also reduce the availability of other nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Phytase enzymes have the ability to hydrolyse phytate, releasing P which reduces the formation of phytatemineral complexes, increasing the bioavailability of minerals (Kornegay et al, 1996, Jalal andScheideler, 2001). In addition to the P and Ca release, inclusion of phytase in the diet may reduce the negative impact of phytate on AA and starch digestion, improving digestibility of dietary AA and energy.…”
Section: Introductionmentioning
confidence: 99%